A Beam Steering Dielectric Resonator Antenna Designed Using Rogers RO4003C Material for S-Band Applications. (10th October 2022) - Kumari, Manisha; Rao, Tavanam Venkata; Jayakar, S. Arun; Srinivas, D.; Padhan, Dola Gobinda; Reddy, A. Kishore; Reddy, P. Rahul; Tura, Amanuel Diriba
Abstract : A pattern reconfigurable dielectric resonator antenna emitting at 3.1 GHz is presented in this study. The beam can be steered at 6 degrees, 8 degrees, 14 degrees, and 171 degrees. Three P-i-N diodes are employed in the slots of the ground plane to help steer the beam direction. By changing the state of the three diodes, five states can be obtained. The TE01 δ mode is excited using a differential feed technique. Differential feed helps in increasing the gain and reducing the size of the structure. The return loss of each state is less than −25 dB. The gain of the first state is 7.65 dBi, the second and fifth state's gain is 8.22 dBi, third and fourth state's gain is 10.6 dBi. This Antenna is designed using Rogers RO4003C material which has low Electrical gravity, low voltage, and high oxidation resistance that makes it appropriate for RF applications. The properties required for RF microwave circuits, matching networks, and controlled impedance transmission lines are present in the RO4003C material. Annealed copper is used for designing the ground plane and feedline which provides excellent conductivity. The antenna is fabricated using the chemical etching process which employs a positive photoresist that gives a higher resolution accuracy for the designed antenna. This process of fabrication has another advantage of inculcating structures from simpler to complex.